The Impact of Artificial Intelligence's Automatic Targeting on Traditional Online Games Cheating - Hu, Yixuan (International Journal of Computer Science and Information Technology, 2024)
With the continuous enhancement of people's spiritual pursuits, multiplayer online games have become a popular trend, encompassing both multiplayer cooperative and competitive games. In multiplayer competitive games, skill disparities among players can lead to unfair competition, prompting some players to resort to cheating for an advantage. Traditional cheating methods, such as memory injection to modify game data, while effective, are easily detectable. In recent years, with the rapid development of Artificial Intelligence (AI) technology, AI-based image recognition cheating software has emerged as a new trend. This software analyzes game screens to identify enemy positions and simulates human operations for automatic aiming, making it difficult for anti-cheating systems to detect. However, AI cheating software has high hardware requirements and is affected by game environments, such as smoke grenades and walls, which can limit its effectiveness. This study aims to explore the advantages and limitations of AI image recognition cheating software compared to traditional memory injection cheating software, analyze the extent of players' use of AI cheating software, and discuss strategies for game companies to combat such cheating behaviors. The research finds that AI cheating software offers superior concealment compared to traditional methods but comes with higher costs and usage barriers. Game companies can employ various measures to prevent cheating, including uploading files to servers for detection, monitoring background software, and using AI to detect abnormal mouse movements. Furthermore, the power of the gaming community should not be overlooked, as player supervision and reporting can effectively reduce cheating behaviors.